2002
DOI: 10.1038/sj.ijo.0801995
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, atherosclerosis and the vascular endothelium: mechanisms of reduced nitric oxide bioavailability in obese humans

Abstract: It is now well established that obesity is an independent risk factor for the development of coronary artery atherosclerosis. The maintenance of vascular homeostasis is critically dependent on the continued integrity of vascular endothelial cell function. A key early event in the development of atherosclerosis is thought to be endothelial cell dysfunction. A primary feature of endothelial cell dysfunction is the reduced bioavailability of the signalling molecule nitric oxide (NO), which has important anti athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 153 publications
4
159
0
4
Order By: Relevance
“…27 Other mechanisms that could explain reduced NO generation in T2DM include increased asymmetric dimethyl arginine (ADMA) levels and decreased cofactors required for synthesis of NO. 28 In cultured bovine aortic endothelial cells, 18,19 adiponectin increases NO production by stimulating eNOS expression/ activity via a PI-3 kinase-dependent pathway involving phosphorylation of eNOS at Ser1179 by AMP-activated protein kinase (AMPK). Conversly, transfection of bovine aortic endothelial cells with dominant-inhibitory mutants of AMPK inhibits NO production in response to adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…27 Other mechanisms that could explain reduced NO generation in T2DM include increased asymmetric dimethyl arginine (ADMA) levels and decreased cofactors required for synthesis of NO. 28 In cultured bovine aortic endothelial cells, 18,19 adiponectin increases NO production by stimulating eNOS expression/ activity via a PI-3 kinase-dependent pathway involving phosphorylation of eNOS at Ser1179 by AMP-activated protein kinase (AMPK). Conversly, transfection of bovine aortic endothelial cells with dominant-inhibitory mutants of AMPK inhibits NO production in response to adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports now suggest that obesity impairs vascular function (Williams et al 2002). Obese individuals show an impaired endothelial-mediated vasodilator response to increased blood flow (Arcaro et al 1999), to insulin (Westerbacka et al 1999) and to biochemical agents (Steinberg et al 1996).…”
Section: Endothelial Function and Obesitymentioning
confidence: 99%
“…3 In this context, there is strong evidence that nitric oxide (NO) is critically involved in obesity and its clinical consequences, including cardiovascular disease, diabetes, and especially, hypertension. [4][5][6] Recent studies have shown that obesity reduces NO bioavailability in adolescents, and this alteration has been linked to important cardiovascular diseases. 7,8 Indeed, endothelium-derived NO has a major role in vascular homeostasis, causes vasodilation, prevents platelet and leukocyte adhesion, and inhibits vascular smooth muscle cell migration and proliferation.…”
Section: Introductionmentioning
confidence: 99%